Effects of Microbial Activity and Environmental Parameters on the Degradation of Extracellular Environmental DNA from a Eutrophic Lake - Zulkefli, Nur Syahidah (Int J Environ Res Public Health, 2019)
Extracellular DNA (exDNA) pool in aquatic environments is a valuable source for biomonitoring and bioassessment. However, degradation under particular environmental conditions can hamper exDNA detectability over time. In this study, we analyzed how different biotic and abiotic factors affect the degradation rate of extracellular environmental DNA using 16S rDNA sequences extracted from the sediment of a eutrophic lake and Anabaena variabilis cultured in the laboratory. We exposed the extracted exDNA to different levels of temperature, light, pH, and bacterial activity, and quantitatively analyzed the concentration of exDNA during 4 days. The solution containing bacteria for microbial activity treatment was obtained from the lake sediment using four consecutive steps of filtration; two mesh filters (100 μm and 60 μm mesh) and two glass fiber filters (2.7 μm and 1.2 μm pore-sized). We found that temperature individually and in combination with bacterial abundance had significant positive effects on the degradation of exDNA. The highest degradation rate was observed in samples exposed to high microbial activity, where exDNA was completely degraded within 1 day at a rate of 3.27 day(−1). Light intensity and pH had no significant effects on degradation rate of exDNA. Our results indicate that degradation of exDNA in freshwater ecosystems is driven by the combination of both biotic and abiotic factors and it may occur very fast under particular conditions.